Waters Masses in the Canary Current Large Marine Ecosystem - Pastor, M.V.; Vélez-Belchí, Pedro; Hernández-Guerra, A. (UNESCO-IOC, 2015)
In the Canary Current Large Marine Ecosystem (CCLME) water masses of very different origin converge. The upper levels, between 100 dbar and 700 dbar, are occupied by North Atlantic Central Waters (NACW) and South Atlantic Central Waters (SACW) that feed the nutrient-rich wind-driven upwelling ecosystem. The NACW are formed by surface subduction of winter water in the North Atlantic, while the SACW are formed in the western South Atlantic Ocean. The Cape Verde Frontal Zone (CVFZ), at approximately 15°N, separates these thermocline waters. The Antarctic Intermediate Water (AAIW) and the warmer and saltier Mediterranean Water (MW) occupy the intermediate layer, between 700 dbar and 1500 dbar. The North Atlantic Deep Water (NADW), formed in the Labrador Sea, occupies the layers deeper than 1500 dbar.